Active-Arm Passive-Leg Exercise Improves Cardiovascular Function in Spinal Cord Injury. (November 2015) - West, Christopher R.; Currie, Katharine D.; Gee, Cameron; Krassioukov, Andrei V.; Borisoff, Jaimie
Abstract : ABSTRACT: In a 43-yr-old male subject with a chronic T3 AIS A spinal cord injury, the acute cardiorespiratory responses to active upper-extremity exercise alone and combined active-arm passive-leg exercise (AAPLE) were investigated, along with the cardiorespiratory, cardiac, vascular, and body composition responses to a 6-wk AAPLE interval training intervention. AAPLE elicited superior acute maximal cardiorespiratory responses compared with upper-extremity exercise alone. In response to a 6-wk interval training regimen, AAPLE caused a 25% increase in peak oxygen uptake, a 10% increase in resting stroke volume, and a 4-fold increase in brachial artery blood flow. Conversely, there were no changes in femoral arterial function, body composition, or bone mineral density in response to training. As a potential clinical intervention, AAPLE may be advantageous over other forms of currently available exercise, owing to the minimal setup time and cost involved and the nonreliance on specialized equipment that is required for other exercise modalities. Abstract : Supplemental digital content is available in the text.